Investigation of the Effect of Initial Graft Tension During Anterior Talofibular Ligament Reconstruction on Ankle Kinematics, Laxity, and In-situ Force. Issue 3 (14th September 2018) - Sakakibara, Yuzuru; Teramoto, Atsushi; Kamiya, Tomoaki; Watanabe, Kota; Yamashita, Toshihiko
Category: Basic Sciences/Biologics Introduction/Purpose: Ankle sprains are the most common sports injuries, and anterior talofibular ligament (ATFL) injury comprised 85% of all ankle sprains. Most patients recover with conservative treatment, but 20% of them progress to chronic ankle instability. Some studies have reported that anatomic reconstruction using a tendon graft is one of the best procedures to restore the ankle to its condition before symptom development. However, the effect of initial graft tension during ATFL reconstruction is still unclear. Therefore, the objective of this study was to investigate the effect of the initial graft tension during ATFL reconstruction. Methods: Eight fresh-frozen cadaveric ankle specimens were subjected to passive plantarflexion (PF)-dorsiflexion (DF) movement from 15° DF to 30° PF using the 6-degree-freedom robotic system. In addition, 60 N of anterior-posterior load, 1.7 Nm of inversion-eversion (IV-EV) torque, and 1.7 Nm of internal-external rotation (IR-ER) torque were applied to the ankle. During testing, 3-dimensional paths of the ankle were recorded simultaneously. Furthermore, in-situ forces of the ATFL and reconstructed graft were calculated using the principle of superposition. A repeated experiment was designed with the intact condition (intact), ATFL transection, and ATFL reconstruction with four different initial graft tensions (10 N, 30 N, 50 N, and 70 N). Results: AP laxity, IV-EV laxity and IR-ER laxity with ATFL transection was significantly greater than those with intact. In ATFL transection, the talus was significantly translated anteriorly with inversion and internal rotations under passive PF-DF motion compared with intact. Kinematic patterns and laxity in ATFL reconstruction with initial tension of 10 N and 30 N almost imitated intact, but in ATFL reconstruction with initial tension 70 N, the talus was significantly translated with external rotation compared with intact. As the initial graft tension during ATFL reconstruction increased, in-situ force of the reconstructed graft tended to increase during PF-DF motion. In-situ force of the reconstructed graft tension was significantly greater with initial tensions of 50 N, and 70 N than with intact during PF-DF motion (Figure 1). Conclusion: ATFL deficiency altered ankle kinematics and laxity. Although the optimal initial graft tension during ATFL reconstruction might restore ankle kinematics and laxity, excessive initial graft tension caused abnormal kinematics and laxity. Furthermore, the reconstructed graft tension increased as the initial tension increased. Initial tension during ATFL reconstruction has the important effect of imitating the normal ankle condition. We suggest that over-tensioning during ATFL reconstruction should be avoided in order to imitate the conditions of a normal ankle.